The dream medium: Robert Edmond Jones' theatre of the future. Issue 1 (2nd January 2016) - Brown, Kevin
ABSTRACT: In the late 1920s, American scenic designer Robert Edmond Jones conceived of the 'New Theatre', a hybrid art form created through the combination of theatre and cinema. For Jones, this strategy's function was to illuminate what he called the 'dual nature' of humanity. By examining Jones' largely ignored and forgotten writings on what he called 'the dream medium', we can gain insight into new ways of utilizing combinations of living actors and media to inspire us and lead us to a deeper understanding of what it means to be human. Jones saw a multitude of benefits from such an arrangement, including as a way to tap into the unconscious world of the inner self and dreams. Jones saw the relationship between the body of the actor and the projected image as the relationship between the 'outer' and 'inner' eye – the conscious and the unconscious. These methods, first proposed by Jones, are being used in contemporary performance to explore the dual nature of self and to disrupt and dislocate singular notions of identity. Jones hoped the New Theatre would bring new life to the art form by speaking to the audience in new ways, and heal them psychologically and spiritually.